Translation as a Factor of Social Teleonomy - Tyulenev, Sergey (TTR)

(untitled) (Association canadienne de traductologie, 2011)
This article considers translation as a factor in the genesis of social macro-formations—ethnoses and superethnoses. The research combines Niklas Luhmann’s social systems theory, Lem Gumilev’s theory of ethnogenesis and the concept of teleonomy borrowed from evolutionary biologist Ernst Mayr in order to demonstrate the ethnogenetic function of translation. An ethnos is a closed loose system; it has a life cycle which is teleonomic by nature. Ethnoses evolve by passing through different stages—from inception to consummation at the acmetic phase and finally into the post-acmetic succession of phases leading to disintegration. At each of these different stages, the social system requires inputs of varying intensity from the environment. Translation as a boundary phenomenon serves as a mechanism to ensure such inputs. From the standpoint of its social function, translation is theorized in a broader sense than usual—as mediation on intrapersonal, interpersonal, interethnic and intergenerational levels.